Synthesis, characterization and antifungal assessment of optically active bis-organotin compounds derived from (S)-BINOL diesters - Costantino, Andrea Rosana (2019)
Background: Organotin(IV) derivatives have appeared recently as potential biologically active metallopharmaceuticals exhibiting a variety of therapeutic activities. Hence, it is important to study the synthesis of new organotin compounds with low toxicity that may be of pharmacological interest.Objectives:This study focuses on the synthesis of new bis-stannylated derivatives with C2 symmetry that could be tested as antifungal agents against two clinical important fungal species, Cryptococcus neoformans and Candida albicans.Methods:The radical addition of triorganotin hydrides (R3SnH) and diorganotin chlorohydrides (R2ClSnH) to bis-α,β-unsaturated diesters derived from (S)-BINOL led to the corresponding new bis-stannylated derivatives with C2 symmetry. Nine pure organotin compounds were synthesized with defined stereochemistry. Four of them were enantiomerically pure and four were diastereoisomeric mixtures.Results:All new organotin compounds were fully characterized, those with phenyl ligands bonded to tin were the most active compounds against both the strains (Cryptococcus neoformans and Candida albicans), with activity parameters of IC50 close to those of the reference drug (amphotericin B).Conclusion:Nine pure organotin compounds with C2 symmetry were synthesized with defined stereochemistry and their antifungal properties were tested against two clinical important fungi with IC values close to those of the reference drug. The structure-containing preferably two or three phenyl groups joined to the tin atom were highly active against both the strains compared with those possessing tri-n-butyl groups.